Comportamento de cultivares brasileiras de trigo com gene Fhb1 quanto à resistência a giberela - Lombardi, Luciano Leonel (2021)
Wheat is one of the most important cereals in the world. Among the main stresses that limit production, Fusarium Head Blight (FHB) stands out, caused by the fungus Fusarium graminearum. Numerous QTLs are reported for resistance, including Fhb1, present in the Chinese cultivar Sumai-3 and which confers resistance to the spread of infection in the ear (Type II). Resistant Brazilian cultivars show good behavior, but complete resistance to this disease is not known. The objective of this study was to verify the introgression effect of the Fhb1 allele of the cultivar Sumai-3 in two Brazilian cultivars, BRS Parrudo and Quartzo, severity of FHB and on yield components. The work was carried out at Embrapa Wheat, in Passo Fundo. Near-Isogenic Lines (NIL) of the two recurrent cultivars (GR) were developed by backcrossing with the Sumai-3 using molecular markers for the QTL Fhb1. In 2019, inoculation of Fusarium graminearum was carried out in 10 genotypes, 3 NILs BRS Parrudo (P01, P02 and P03); 3 NILs Quartzo (Q01, Q02 and Q03); BRS Parrudo; Quartzo; Sumai-3 and CD116. The genotypes were sown in buckets, in a controlled environment, with a randomized block design and inoculation carried out on the central spikelet in anthesis, with humidity maintained for 48 hours. The evaluations were carried out at 5, 15 and 25 days after inoculation, with a count of infected spikelets. After harvesting, healthy and fusarium damaged kernels (FDK) were counted and weighed. Agronomic characteristics of healthy ears showed great similarity between NIL and their GRs. In the inoculated ears, comparing all genotypes, differences were verified (p>0.01). NIL P01, P02, P03, Q01 and Q03 had the same behavior as Sumai-3 in the variables Healthy grains, Stir-fed grains, Infected spikelets (EI) and Weight of a thousand seeds, in the variable Disease index, they formed an intermediate group, with Sumai-3 being the genotype with the best behavior. NIL Q02, Quartzo and CD116 produced more EI. Comparing NILs with GRs, in BRS Parrudo, only total PMS showed differences, with Quartzo, only healthy and gibberellate PMS showed no differences. Comparing NILs with the cultivars as controls, NILs P had similar behavior to Sumai-3 and GR itself. As for NILs Q, only Q02 in most variables had a behavior equal to CD116 and to GR itself, Q01 and Q03 differed and showed behavior close to Sumai-3. Comparing NILs, in all variables, NIL Q02 had a lower behavior than the other NILs. In disease progress, all genotypes had EI at 5 days. At 15 days there was no progress of the disease only in Sumai-3, BRS Parrudo, P01 and P03, at 25 days Sumai-3 did not progress. Comparing the genotypes at 25 days, in the group with less EI, together with Sumai-3 are Q01, Q03, P01, P02 and P03, already with more EI, CD116 and Quartzo (p<0.05). There was a correlation of most variables, only Incidence showed a low correlation with the other variables. The inoculation guaranteed the infection for disease evaluation, the introgression of FHB1 alleles in BRS Parrudo and Quartzo cultivars did not change the agronomic characteristics related to spike and was effective in increasing resistance to type II FHB.